2020
DOI: 10.3390/su12124990
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Optimal Cost-Benefit Solution for a Low Impact Development Layout by Zoning, as Well as Considering the Inundation Duration and Inundation Depth

Abstract: Urban flooding now occurs frequently and low impact development (LID) has been widely implemented as an effective resilience strategy to improve storm water management. This study constructed the inundation curve to dynamically simulate the disaster, and established an inundation severity indicator (ISI) and cost-effectiveness indicator (CEI) to quantify the severity and cost effectiveness at each site. The study set 10 different density scenarios using a zonal approach. The results showed that LID could reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In contrast, permeable pavements were able to achieve better resilience enhancement with a smaller area [48]. In addition, the study found that the GI combination alternatives resulted in a greater increase in resilience enhancement than the alternatives with just a single type of GI, which is also consistent with previous research findings [86,87]. Overall, the results suggest that the use of GI is effective in increasing the flood resilience of the resilient system [51].…”
Section: The Roles Of Gi In Improving Urban Stormwater Resiliencesupporting
confidence: 89%
“…In contrast, permeable pavements were able to achieve better resilience enhancement with a smaller area [48]. In addition, the study found that the GI combination alternatives resulted in a greater increase in resilience enhancement than the alternatives with just a single type of GI, which is also consistent with previous research findings [86,87]. Overall, the results suggest that the use of GI is effective in increasing the flood resilience of the resilient system [51].…”
Section: The Roles Of Gi In Improving Urban Stormwater Resiliencesupporting
confidence: 89%
“…Comparisons of LID facility prices in Beijing, China, according to SCCTG, further emphasize the cost-effectiveness of green swales (see Table S4 in Supporting Information). Compared to conventional curb and drainage systems such as the rainfall bucket system, the building cost of the green swale system is currently less than 0.20 USD/m 2 and its maintenance cost is only 6% of its construction cost (Wu et al, 2020;Li et al, 2021).…”
Section: Long-term Fundsmentioning
confidence: 99%
“…According to the experience of the authors [5], some of the SUD and LID measures can be implemented in urban areas relatively easily, without substantial technical problems and with reasonable investment costs [206][207][208]. Beyond a certain level, the implementation of these measures starts to raise technical problems, which induce relatively high investment costs, whereas the contribution to runoff reduction is small.…”
Section: Rainfall-runoff Models and The Decision-making Processmentioning
confidence: 99%